Strategi Konservasi Daerah Tangkapan Air Danau Singkarak - M Fadhilah Zaim Umam; Aras Mulyadi; Nofrizal Nofrizal (Pelantar Press, 2024)
Land use changes that occur in the upstream areas of the watershed will certainly result in changes in the hydrological characteristics of the watershed. Area expansion in the form of land conversion, whether into residential or agricultural land, in the process often does not pay attention to soil and water conservation principles. Therefore, sustainable water catchment management is needed to reduce increasing land degradation. This research uses the Descriptive Analysis method through the Multidimensional Scaling approach. The sustainability status of the Lake Singkarak catchment area based on the results of the RapDTA analysis is in the moderately sustainable category with an index value of 54.87%. If we look at each dimension that is included in the quite sustainable category, it is the economic dimension with an index value of 55.10% and the social dimension with an index value of 50.37%, while the ecological dimension has an index value of 49.88%.Â